Patterns of public participation: Opportunity structures and mobilization from a cross-national perspective. Issue 5 (15th August 2016) - Slutsky, Jean; Tumilty, Emma; Max, Catherine; Lu, Lanting; Tantivess, Sripen; Hauegen, Renata Curi; Whitty, Jennifer A; Weale, Albert; Pearson, Steven D; Tugendhaft, Aviva; Wang, Hufeng; Staniszewska, Sophie; et al.
Abstract : Purpose: – The paper summarizes data from 12 countries, chosen to exhibit wide variation, on the role and place of public participation in the setting of priorities. The purpose of this paper is to exhibit cross-national patterns in respect of public participation, linking those differences to institutional features of the countries concerned. Design/methodology/approach: – The approach is an example of case-orientated qualitative assessment of participation practices. It derives its data from the presentation of country case studies by experts on each system. The country cases are located within the historical development of democracy in each country. Findings: – Patterns of participation are widely variable. Participation that is effective through routinized institutional processes appears to be inversely related to contestatory participation that uses political mobilization to challenge the legitimacy of the priority setting process. No system has resolved the conceptual ambiguities that are implicit in the idea of public participation. Originality/value: – The paper draws on a unique collection of country case studies in participatory practice in prioritization, supplementing existing published sources. In showing that contestatory participation plays an important role in a sub-set of these countries it makes an important contribution to the field because it broadens the debate about public participation in priority setting beyond the use of minipublics and the observation of public representatives on decision-making bodies.